Relevansi Hukum Transplantasi Organ dalam Perspektif Hukum Positif dan Fikih Kontemporer di Indonesia - Nadizatul Munirah; Yadira Rizka Aulia; Davin Ade Putra Pratama; Muhammad Alvin Najmi (Jurnal Teologi Islam, 2025)
The advancement of medical technology and the increasing number of organ failure cases have positioned organ transplantation as an essential solution for saving human lives. However, this progress must be accompanied by a comprehensive understanding of legal and ethical frameworks to ensure that transplantation practices remain within humanitarian boundaries and are protected from misuse. This article discusses the urgency of understanding the legal dimensions of organ transplantation in the modern era through an analysis of national regulations, ethical–juridical challenges, and contemporary fiqh perspectives. Based on literature studies and case analyses, it is found that although the legal framework already exists, various issues persist, such as legal uncertainty for donors and recipients, the potential commercialization of organs, and ethical conflicts in practice. Therefore, strengthening regulations, increasing public education, and ensuring synergy between positive law and Islamic legal principles are necessary to guarantee that organ transplantation is carried out lawfully, ethically, and with dignity.